2020
DOI: 10.1186/s12917-020-02317-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase-I trial of survivin inhibition with EZN-3042 in dogs with spontaneous lymphoma

Abstract: Background: Lymphoma is a common cancer in dogs. While most dogs receiving chemotherapy experience remission, very few are cured, and median survival times are generally in the 12-month range. Novel approaches to treatment are unquestionably needed. The Inhibitor of Apoptosis Protein (IAP) family member survivin, which is one of the most commonly overexpressed proteins in human cancer, plays a key role in apoptosis resistance, a major cause of drug-resistant treatment failure. Survivin targeting therapies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In 2017, a study comparing canine tumors of different origins (epithelial, mesenchymal and round-cell tumors) showed that survivin was significantly increased in malignant versus benign tumors (p < 0.05) at the transcriptional level [64]. Finally, in 2020, the survivin inhibitor EZN-3042 was shown to be well-tolerated in a phase I clinical trial of dogs with lymphoma, opening new avenues for the clinical targeting of this protein in veterinary oncology [65].…”
Section: Evasion Of Apoptosis-the Role Of Survivinmentioning
confidence: 99%
“…In 2017, a study comparing canine tumors of different origins (epithelial, mesenchymal and round-cell tumors) showed that survivin was significantly increased in malignant versus benign tumors (p < 0.05) at the transcriptional level [64]. Finally, in 2020, the survivin inhibitor EZN-3042 was shown to be well-tolerated in a phase I clinical trial of dogs with lymphoma, opening new avenues for the clinical targeting of this protein in veterinary oncology [65].…”
Section: Evasion Of Apoptosis-the Role Of Survivinmentioning
confidence: 99%